Music performance anxiety among classical musicians: strategies for improving performance and applications for classical guitarists - Tempera, André Rafael Correia (2018)
Music performance anxiety (MPA) is experienced in varying degrees of intensity by most, if not all, musicians. It is particularly heightened in a classical music environment and if not addressed properly, it may cause significant harm to the careers and even wellbeing of individuals. Performers and teachers usually develop their own valid coping strategies through years of practical experience, but often lack a theoretical understanding of MPA and its mechanisms, considering it to be an insurmountable and career ending affliction. There are several articles and books addressing different aspects of this subject, and this knowledge can be utilized to develop practice and coping strategies, that incorporate practical and scientific information. This integration should be of special interest to the classical musician community in several aspects of performance and pedagogy, and particularly, for the future generations of musicians who often feel are not being adequately prepared for the reality of a performing career. Differentiating factors such as personality, age and gender are related to the way individuals perceive and experience performance anxiety. Another, somewhat understudied relation, is how the specificities of each instrumentalist affect, and are affected by MPA. By characterizing classical guitarists and their particularities, it is possible to ascertain if this sub-group of musicians has specific needs, and which are the best approaches for them to address music performance anxiety issues. This dissertation attempts to improve classical musicians’ understanding of MPA and will hopefully contribute to a more effective approach to this issue within the community; Resumo: Ansiedade na performance musical dos músicos eruditos: Estratégias para melhorar a performance e aplicações para guitarristas clássicos - A ansiedade na performance musical (APM) é sentida em vários graus de intensidade pela maioria, senão a totalidade, dos músicos. É particularmente elevada no ambiente da música erudita e, quando não é abordada de forma adequada, pode causar danos significativos nas carreiras e até na saúde das pessoas. Intérpretes e professores normalmente desenvolvem as suas próprias estratégias de coping através de anos de experiência prática, mas frequentemente carecem de uma compreensão da APM e dos seus mecanismos, considerando-a como uma condição insuperável que pode ditar o fim de uma carreira. Existem diversos artigos e livros dedicados a uma grande quantidade de aspectos associados a este tema, e este conhecimento facilita o desenvolvimento de estratégias para o estudo da música e para coping, incorporando informação prática e científica. Esta integração deve ser de particular interesse para a comunidade dos músicos eruditos em diversos aspectos da performance e da pedagogia, e particularmente, para as futuras gerações de músicos que frequentemente sentem não estar a ser adequadamente preparados para a realidade de uma carreira como intérpretes. Factores diferenciadores tais como personalidade, idade e sexo estão relacionados com a forma como os indivíduos interpretam e experienciam a ansiedade. Outra relação, algo negligenciada, é a de como as especificidades de cada instrumento afectam e são afectadas pela APM. Ao caracterizar os guitarristas clássicos e as suas particularidades, torna-se possível aferir se este sub-grupo de músicos possui necessidades específicas e quais são as melhores abordagens para resolver problemas relacionados com a ansiedade na performance musical. Esta dissertação tenciona melhorar a compreensão da APM por parte dos músicos eruditos e contribuir para que este assunto seja abordado de uma forma mais eficaz pela comunidade.